Media Accountability Online in Israel. An application of Bourdieu's field theory - Ronja Kniep (Global Media Journal: German Edition, 2015)
Due to structural changes in journalism, such as deregulation, privatisation and the influence of new technologies, it has become increasingly important to study media accountability (MA). By applying Bourdieu's theory of social fields, this paper proposes a new approach to do so: MA is defined as a function of both journalistic autonomy and influence in the media field. Here, online communication potentially widens the scope of action for media's transparency, responsiveness as well as the articulation of media criticism by a variety of actors. In Israel, media criticism is driven by the agent's struggle for interpretive authority over public discourse in a politically polarized society. Semi-structured interviews with Israeli journalists, media activists and experts suggest that journalistic agents who have yet to earn credibility and reputation exploit online communication to its full potential, while agents in the field of power tend to dismiss online criticism. The influence of the audience's media criticism is not solely dependent on the technical ability of connecting and hearing the voices of the masses; it has to be in combination with symbolic or political capital. However, the demand for media's social responsibility is also related to being more careful and less critical, which is very evident in Israel. Thus, it is important to critically reflect on what happens when media accountability practices become more efficient and a stronger sense for “being watched” develops.
urn:nbn:de:gbv:547-201500645
Keywords: 330; online communication; journalism; field theory; Bourdieu; Israel; media accountability